KEMAMPUAN PESERTA DIDIK DALAM MENGEMBANGKAN KREATIVITAS PADA PEMBELAJARAN SENI RUPA MELALUI KARYA SENI GRAFIS DENGAN TEKNIK PERCIK DI KELAS II SD NEGERI 30 SABANG - Aristi, Alif Restu; Mislinawati, Mislinawati; Fitri, Aida (Elementary Education Research, 2023)
Basically, all humans have creative talents in themselves, but each student has different abilities from one another so how to be developed and facilitated so that the potential can develop properly. This study aims to describe the ability of students to develop creativity in fine arts learning through graphic art works with splashing techniques in grade II SD Negeri 30 Sabang. The approach taken is qualitative with a descriptive type of research. The subjects in this study were class II students totaling 21 people. Data collection is carried out by observation techniques and performance tests (the assessment results of the performance test are obtained from the assessment of the products produced). All collected data will be processed with data analysis stages, namely data reduction, data presentation and drawing conclusions. The results of this study show that the average score obtained by grade II students is 72.42 this is based on the assessment criteria for color composition aspects reaching 85% with good categories, creativity aspects reaching 75% with sufficient categories, neatness aspects of works reaching 60% with less categories and beauty aspects reaching 75% with sufficient categories. So that it is known that there are 6 students who are very good with a percentage of 29%, 3 students who are well-capable with a percentage of 14%, 3 students who are quite capable with a percentage of 14% and there are 9 students who are less capable with a percentage of 43%, and it can be concluded that grade II students at SD Negeri 30 Sabang already have a fairly good ability in developing creativity through artwork graphics using splashing techniques.